Značilnosti tokov okroglega lesa v letu 2014 - Piškur, Mitja (Gozdarski vestnik, 2015)
According to the temporary data, production of forest wood assortments exceeded five million "net" cubic meters in 2014. Large production size was primarily a consequence of the ice break sanitation. Several factors coincided last year: large stocks of wood in the industry at the beginning of the year, reduction of consumption of lower quality wood in Austria, and large supply due to the consequences of the ice break sanitation. Such great imbalance between supply and demand led to price reduction, which had also been the case in other European countries after disasters in the past.
Keywords: les; tokovi okroglega lesa; žled; Slovenia; Slovenija; zunanja trgovina